Feeding Possibilities for Influencing the Fatty Acid Composition of Broiler Body - Pálfy, Tamás; Gungel, János (Acta Agraria Debreceniensis, 2005)
The experiment was conducted to assess the effect of feeding lard, linseed oil, sunflower oil and soya oil on performance, chemical and fatty acid composition of broilers. The experiment was carried out with 1200 Ross-308 male broilers. They were fed 3 phase diets. These diets were isonitrogenous, isoenergetic and contained 6% oil. The result of the experiment shows no effect of different oil sources on growth performance in male broilers, however the fatty acid composition differed (p<0,05).